Applying a Coastal Vulnerability Index (CVI) to the Westfjords, Iceland : a preliminary assessment - Davies, William Thomas Ronald, 1985- (2012)
Coastal environments are of significant economic, ecological and social importance to the global population. However, they are under increasing pressure from both rapid anthropogenic development and predicted consequences of climate change, such as sea-level rise, coastal erosion and extreme weather events. In light of this, effective coastal management is necessary to ensure the conservation and prosperity of these important environments. Coastal vulnerability assessments are a useful means of identifying areas of coastline that are vulnerable to impacts of climate change and coastal processes, highlighting potential problem areas. These assessments often take the form of an ‘index’ that quantifies the relative vulnerability along a coastline. This preliminary assessment adapted a coastal vulnerability index (CVI) methodology applied in the KwaZulu-Natal province, South Africa to the fjordic environment of the Westfjords, Iceland. By measuring prescribed physical parameters, the study evaluatedthe relative coastal vulnerability of the Westfjords coastline to impacts of sea-level rise, erosion and extreme weather events and subsequently assessedsocio-economic features located in particularly vulnerable areas. Furthermore, the methodology was adapted to incorporate Westfjords specific hazards e.g. avalanche risk. The majority of coastal sections scored similarly: in a possible range of 6-28, 66% of coastal sections scored between 15-18.Areas that were ranked as higher vulnerability were scattered across the study area with no real geographical association, although two of the three highest scoring coastal sections were located in Dýrafjörður. Seven of the eight highest scoring coastal sectionswere situated in an estuary environment. Other common higher score determinants were short beach width, high avalanche risk and minimal vegetation behind the back-beach. Transport infrastructure was present in all but one of the coastal sections scoring 22 and above, ranging from major to minor roads. Other socio-economic ...